Corporate environmental footprint and product market competition - Grinstein, Yaniv; Larkin, Yelena (Journal of Financial Intermediation, 2025)
• How does product market competition affect corporate environmental footprint? • We examine restructuring of U.S. electric utilities, the number one emissions-intensive sector. • Cost-cutting actions are the key driver of changes in operations and emissions of electric plants. • Cost-cutting actions lower environmental footprint when plant technology allows greener production. • Without such technology, competition worsens environmental outcomes. Banks face pressure to integrate a wider range of risks into lending decisions, including both traditional product-market risks and the increasingly important environmental risk. Yet how these two types of risk interact remains unclear. We show that production technology is pivotal in shaping the impact of product-market competition on environmental risk. Focusing on the restructuring of the US electric utility industry, which introduced product-market competition into a highly polluting sector, we find that technological capacity is key. When technology enables cost-saving production decisions that also improve environmental performance, competition reduces environmental footprint. Otherwise, it exacerbates it. These findings suggest that lenders must assess not only individual risk factors of borrowers but also their potential interactions, with firms’ technological capacity playing a crucial role.